History of Lithuanian and Old Prussian Names in the Documents of the German Order - Ivoška, Darius (Onomástica desde América Latina, 2025)
This article explores the role of authentic archival legal, administrative, and diplomatic documents from the Middle Ages and later periods in researching Old Prussian and Lithuanian historical names. It aims to highlight the critical role of German Order documents in preserving the old Baltic onomasticon, focusing on examples from the Prussian and Lithuanian naming systems. The article employs critical comparative analysis of historical documents, name reconstruction methods, and graphemic-morphemic analysis, which reveal that authentic archival documents serve as the primary and most reliable sources of empirical material, while historiographic works are essential for verifying the collected data. The topic is crucial for scholars of both linguistics and history research fields, and is broadly discussed in numerous scientific works. A detailed examination of two Old Prussian and Lithuanian historical personal names illustrates not only the depth of specific name studies but also the impact of synchronic and diachronic analysis on research outcomes. This article also underscores the continuity of research into the Old Prussian and Lithuanian historical onomasticon, leveraging peripheral contextual data to support hypotheses in challenging nomenclature cases. It emphasizes the need for further investigation into historical onomastics, particularly of extinct languages, through the discovery of new sources of empirical material. In this way, the knowledge about the Old Prussian nomenclature is refined, especially when trying to identify the formation of Old Prussian personal names, and on the basis of this, to determine the etymology. Precisely determining the etymology of the names of a extinct language is an essential factor in assessing not only the origin of the name, but also the possible impact of the use of foreign languages on it.